There is no visible symbol between 4x and 2.
There is no visible symbol between 4x and 2.
There is no visible symbol between 4x and 2.
There is no visible symbol between 4x and 2.
There is no visible symbol between 4x and 2.
-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]
(2x - 3)(4x + 9)(2x + 3) = (2x - 3)(2x + 3)(4x + 9) = [(2x)^2 - (3^2)](4x + 9) = (4x^2 - 9)(4x + 9) = (4x^2)(4x) + (4x^2)(9) - (9)(4x) - (9)(9) = 16x^3 + 36 x^2 - 36x - 81
4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3
2x - 5 - 4x + 8= 2x - 4x - 5 + 8= -2x + 3
2x+17 = 4x-3 2x-4x = -3-17 -2x = -20 Answer: x =10
4x - 2x = 2x
If that's - 4x, the answer is (2x + 3)(2x - 5) If that's + 4x, the answer is (2x - 3)(2x + 5)
-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]
(2x - 3)(4x + 9)(2x + 3) = (2x - 3)(2x + 3)(4x + 9) = [(2x)^2 - (3^2)](4x + 9) = (4x^2 - 9)(4x + 9) = (4x^2)(4x) + (4x^2)(9) - (9)(4x) - (9)(9) = 16x^3 + 36 x^2 - 36x - 81
2x
4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3
2x - 5 - 4x + 8= 2x - 4x - 5 + 8= -2x + 3
2x+17 = 4x-3 2x-4x = -3-17 -2x = -20 Answer: x =10
4x - 7 = 2x + 15 4x = 2x +222x = 22x = 11
4x-1=2x+1
2x + 4x - x = 5x
8x-2x+4x=10x